Reconstruction of the Regulation on the Cancellation of Arbitration Awards by Courts in the Indonesian Legal System Based on the Principle of Finality of Arbitration and Limitation of Judicial Intervention - Cepi Hendrayani; Effendy Lod Simanjutak (International Journal of Social Service and Research, 2026)
Arbitration is a dispute resolution forum that upholds the principle of finality, whereby an arbitral award is final and binding on the parties. The finality of arbitral awards is a fundamental principle underlying the success of non-litigation dispute resolution mechanisms. However, in Indonesian practice, the mechanism for annulling arbitral awards through the courts is often used as an instrument of judicial intervention that weakens the finality of arbitration. This research aims to analyze the regulatory disharmony concerning the annulment of arbitral awards under Law Number 30 of 1999 and Indonesian judicial practice, and to compare it with several other legal systems. This research uses a comparative legal method with statutory, conceptual, comparative, and case study approaches by comparing the Indonesian arbitration system with those of Singapore under the International Arbitration Act, England under the Arbitration Act 1996, and the UNCITRAL Model Law. The research findings indicate that unclear boundaries of court authority, the absence of technical guidelines for judges, and a culture of judicial supremacy are the main causes of the ineffectiveness of arbitration finality in Indonesia. This research concludes that regulatory reconstruction is needed to align national standards with international practices by affirming the limits of judicial intervention, establishing Supreme Court regulations, enhancing judicial specialization, and harmonizing national arbitration law with the UNCITRAL Model Law in order to strengthen legal certainty and attract investment in Indonesia.